The Concept of Yoga in the Tattwa Jñana Script - Widya Sena, I Gusti Made (Analisa: Journal of Social Science and Religion, 2021)
Various lontar and Tattwa scripts in Bali are the fruit of local wisdom inspired by the teachings of the Vedic scriptures. This local script is based on the truth that has been guiding most Balinese people. One of the Tattwa truths written in the Vedas is the concept of yoga as a means to attain spiritual awareness. Yoga offers a holistic, practical and religious approach that aims to help all components of the body work together in harmony. This text contains theology, cosmology, and practice of the teachings of Prayogasandhi (tapa, brata, yoga and samadhi) knowledge to save souls from misery. This study aims to understand the concept of Yoga in the Tattwa Jñana Script as a way to achieve spiritual awareness. The theory used is structural theory and semiotic theory. This study uses the method of collecting data documents and literature. The data analysis technique was carried out qualitatively by describing it descriptively. The results of this study indicate that: (1) The Tattwa Jñana script consists of prose which is divided into several chapters, and consists of 74 slokas in Old Javanese. (2) The concept of yoga in the Tattwa Jñana script is Prayogasandhi. Prayogasandhi is a means to attain spiritual awareness through tapas, brata, yoga and samadhi to Iswara (God). Prayogasandhi needs to be followed by discipline, true knowledge (samyagjna) and contemplation.